From Awareness to Action: The Influence of Digital Tax Education and Tax Literacy on Behavioral Compliance Following Coretax Implementation in Indonesia - Sylvia Marcellina; Agus Munandar; Vugar Abdullayev (International Journal of Educational Narratives, 2026)
Background. Digital tax systems are increasingly expected not only to improve administrative efficiency but also to foster taxpayer learning and compliance. This issue is particularly relevant in Indonesia following the implementation of Coretax, a digital tax system designed to integrate tax services and strengthen compliance. However, the effectiveness of digital tax reform remains uncertain because technological adoption alone may not be sufficient to encourage compliant behavior without adequate tax literacy and taxpayer awareness. Previous studies have largely emphasized system performance and technology acceptance, while the educational and behavioral roles of digital tax systems remain underexplored. Purpose. This study examines the effects of tax literacy, taxpayer awareness, and Coretax implementation on behavioral tax compliance among individual taxpayers, with Coretax positioned as a digital learning platform that may support taxpayer understanding and compliance behavior. Method. A quantitative approach was employed involving 100 individual taxpayers registered at the Kalideres Primary Tax Office, Jakarta. Data were collected through structured questionnaires and analyzed using PLS-SEM. Results. Tax literacy and taxpayer awareness significantly and positively influence behavioral tax compliance, with taxpayer awareness emerging as the strongest predictor. Coretax implementation also has a significant positive effect, although its contribution is weaker than the educational and psychological factors. Conclusion. Digital tax systems can support behavioral tax compliance when complemented by adequate tax literacy and taxpayer awareness. This study contributes to the literature by positioning Coretax not only as an e-government system but also as a digital learning platform that links technological, educational, and behavioral dimensions of taxpayer compliance.